2021
DOI: 10.1080/09500782.2021.1933018
|View full text |Cite
|
Sign up to set email alerts
|

To integrate a language focus in a linguistically diverse physics classroom

Abstract: It has previously been suggested that there is a need for a more language focused science instruction, especially in linguistically diverse classrooms, where many students are second language learners. But it has also been suggested that teachers may feel uncertainty about how to teach in ways that promote learning of both subject matter and language. Previous studies have revealed how the language of science, especially the written language of science, is used to create a certain meaning. Research on interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The difficulties cover language, cultural, cognitive, and social elements (Rahmat, 2019). ESL students have distinct academic obstacles as they negotiate the complex attempt of acquiring a second language while concurrently struggling with subject-specific information in disciplines (Uddling, 2022). Consequently, there is an inherent necessity for pedagogical methodologies that demonstrate sensitivity towards the language origins of these students and the adaptability to accommodate their progressing degrees of skill and comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties cover language, cultural, cognitive, and social elements (Rahmat, 2019). ESL students have distinct academic obstacles as they negotiate the complex attempt of acquiring a second language while concurrently struggling with subject-specific information in disciplines (Uddling, 2022). Consequently, there is an inherent necessity for pedagogical methodologies that demonstrate sensitivity towards the language origins of these students and the adaptability to accommodate their progressing degrees of skill and comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…Thereto, mainly focusing on the verbal language demands of science (speech and writing), several studies have shown how science teachers in linguistically diverse classes (for a definition, see Materials and Methods) can increase the students' participation and learning opportunities by explicitly unpacking the language demands and by encouraging the students to express themselves scientifically [13][14][15][16]. Furthermore, research has proven that it is important that teachers in linguistically diverse classes tune in to the students' prior content knowledge including their level and use of scientific language [15,17,18]. Hence, in science teaching and learning, and in particular for students learning the language of instruction and subject content in parallel, teachers need to have a dual focus on multimodal aspects of meaning making in their subjects.…”
Section: Introductionmentioning
confidence: 99%